2018
DOI: 10.1186/s12935-018-0591-2
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in lncRNA AC016683.6 and its interaction with smoking exposure on the susceptibility of lung cancer

Abstract: BackgroundLong non-coding RNAs play pivotal roles in the carcinogenesis of multiple types of cancers. This study is firstly to evaluate influence of rs4848320 and rs1110839 polymorphisms in long non-coding RNA AC016683.6 on the susceptibility of lung cancer.MethodsThe present study was a hospital-based case–control study with 434 lung cancer patients and 593 cancer-free controls. Genotyping of the two SNPs detected by Taqman® allelic discrimination method.ResultsThere were no statistically significant associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Conversely, there were no statistically significant associations between rs4848320 and rs1110839 in AC016683.6 lncRNA and risk of lung cancer. However, by performing a stratification analysis based on environmental risks, both polymorphisms significantly increased the risk of lung cancer in dominant and homozygous models of smoking exposure [36]. LncRNA maternal expressed-gene 3 (MEG3) rs4081134 SNP was significantly associated with lung cancer susceptibility in a dominant model in the Chinese population [37].…”
Section: Methods For Detection Of Snps and Measurement Of Associatmentioning
confidence: 99%
“…Conversely, there were no statistically significant associations between rs4848320 and rs1110839 in AC016683.6 lncRNA and risk of lung cancer. However, by performing a stratification analysis based on environmental risks, both polymorphisms significantly increased the risk of lung cancer in dominant and homozygous models of smoking exposure [36]. LncRNA maternal expressed-gene 3 (MEG3) rs4081134 SNP was significantly associated with lung cancer susceptibility in a dominant model in the Chinese population [37].…”
Section: Methods For Detection Of Snps and Measurement Of Associatmentioning
confidence: 99%
“…Cases were from several hospitals in Shenyang. Inclusion and exclusion criteria of the cases were mentioned in our previous studies [39,[45][46][47]. And the healthy controls were from medical examination centers of hospital.…”
Section: Study Subjects and Data Collectionmentioning
confidence: 99%
“…Up to now, some researches have demonstrated that cigarette smoking or exposure may be associated with the expression of lncRNAs in lung cancer patients. Li J et al [ 27 ] found that polymorphisms in lncRNA AC016683.6 significantly increased the risk of lung cancer in the smoking population. Lv X et al also reported that there were significant interactions of lncRNA AC008392.1 polymorphisms with smoking exposure to lung cancer susceptibility [ 28 ].…”
Section: Discussionmentioning
confidence: 99%